USAHATANI, PENDAPATAN DAN KESEJAHTERAAN PETANI KOPI DI LAMPUNG BARAT - Rafika Tania; Sudarma Widjaya; Ani Suryani (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2019)
The purposes of this research were to analyze the level of household income and the welfare of coffee farmers in Gunung Terang Village, Air Hitam District, West Lampung Regency.  This research location was chosen purposively in Gunung Terang Village, Air Hitam District, West Lampung Regency.  The research was conducted by survey method.  Data collection was carried out in October 2017 until November 2017.  The sample size was 40 coffee farmers who were drawn by simple random sampling technique.  The analysis used analysis of farm income and household welfare according to Sayogyo criteria.  The results of this study indicate that the average household income of coffee farmers in Gunung Terang Village, Air Hitam Subdistrict, West Lampung Regency were relatively high and the welfare of coffee farmer households based on Sayogyo criteria were categorize as prosperous.Key words: coffee, income, prosperity